Sustainable Urban Cells and the Energy Transect Modeling: Reconciling the Green and the Urban - Elisabetta Troglio; Tigran Haas (European Regional Science Association (ERSA), 2013)
The global city of the 21st century faces major challenges & crises, including social and economic stratification, wasteful consumption of resources, transportation congestion, and environmental degradation with the omnipresence of global climate change. Our cities, communities and neighborhoods are undergoing also rapid transformation and retrofits in terms of energy efficiency and climatic adaptations almost to the point of drastic environmental determinism. The discussion in this paper explores ways for raising quality of life and the standard of living in a new modern era by creating better and more viable places to live through sustainable urbanism approaches. The assertion is that the Green (Sustainable) Urbanism approaches offer an environmentally sound way to plan and design more ecologically stable communities. Sustainable Urban Cells within the idea of the Urban Energy Transect is presented here as a new quantitative and qualitative modeling approach and analytical methodology in working with planning of sustainable urban communities, compatible with other analytical tools such as Space Syntax and other GIS tools. The empirical cases (Sweden and Italy) introduced, show how a better understanding of an integrated system of zoning in a complex community urban setting can contribute to clearer planning and energy efficiency of buildings. The questions we raise are: How can we combat and reconcile urban growth with sustainable use of resources for future generations to thrive? Where and how urbanism comes into the picture? and what role ?sustainable? urban forms can play and have in light of these events? These and some other issues are tackled in this paper whose conclusions point to the predilection that beyond being a system of classification, the cell + transect model we present in this paper, has also the potential to become a better instrument for planning & design which would simply result in better places to live.
Keywords: 330; Energy; Urban Transect; Green urbanism; sustainability; cells